Guyana emergent : the post-independence struggle for nondependent development - Manley, Robert H. (G.K Hall & Co. BostonUS, 1979)
Examines the strategies pursued during the country's first post-independence decade by its political leadership for transition from dependence and for achieving, maintaining or enhancing their own power. Also considers the role the country has played in Caribbean integration and in leading among Commonwealth nations of the region, decolonisation and other aspects of ideological re-orientation.